La géographie juridique. Recherche et limite d’une définition - Jean-François Boudet (Développement Durable et Territoires)
The confluence of geography and law is very old and everyone has tried to classify its geography data in groups and sub-groups. That initiative look like difficulty in a globalized political economics, in such a way the inherited legal would help to understand and to define the “legal geography” as a simple ideology.